(untitled) - Makofske, David B; Donahoo, Michael J. (Amsterdam ; Boston, 2004)
5 chapters: Introduction; Basic Sockets; Sending and Receiving Messages; Beyond the Basics; Under the Hood;; Bibliography: 171 - 172
Keywords: Computer software -- Application program interfaces ; Computer network protocol -- TCP/IP; Computer program language -- C#; Phần mềm máy tính -- Giao diện chương trình ứng dụng; Giao thức mạng máy tính -- TCP / IP; Công nghệ thông tin -- Ngôn ngữ lập trình -- C#